2019
DOI: 10.1002/jor.24519
|View full text |Cite
|
Sign up to set email alerts
|

Combined Injury to the ACL and Lateral Meniscus Alters the Geometry of Articular Cartilage and Meniscus Soon After Initial Trauma

Abstract: Combined injury to the anterior cruciate ligament (ACL) and meniscus is associated with earlier onset and increased rates of post‐traumatic osteoarthritis compared with isolated ACL injury. However, little is known about the initial changes in joint structure associated with these different types of trauma. We hypothesized that trauma to the ACL and lateral meniscus has an immediate effect on morphometry of the articular cartilage and meniscus about the entire tibial plateau that is more pronounced than an ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…This is an important concern, as we observed a much larger area of ACLR subjects cartilage demonstrated thickening. Our prior investigation of subjects suffering a first‐time noncontact ACL rupture, demonstrated that the thickness of medial tibial articular cartilage changes within days following the index ACL trauma 3,24 . Indeed, soon after the index injury, and before surgery, the thickness of the tibial articular cartilage in the areas of the medial compartment of the tibia of the ACL injured females underwent thickening and thinning relative to the contralateral normal knee 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important concern, as we observed a much larger area of ACLR subjects cartilage demonstrated thickening. Our prior investigation of subjects suffering a first‐time noncontact ACL rupture, demonstrated that the thickness of medial tibial articular cartilage changes within days following the index ACL trauma 3,24 . Indeed, soon after the index injury, and before surgery, the thickness of the tibial articular cartilage in the areas of the medial compartment of the tibia of the ACL injured females underwent thickening and thinning relative to the contralateral normal knee 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Our prior investigation of subjects suffering a first-time noncontact ACL rupture, demonstrated that the thickness of medial tibial articular cartilage changes within days following the index ACL trauma. 3,24 Indeed, soon after the index injury, and before surgery, the thickness of the tibial articular cartilage in the areas of the medial compartment of the tibia of the ACL injured females underwent thickening and thinning relative to the contralateral normal knee. 3 In the current study examining ACLR subjects, we found the location of the areas that underwent thickening and thinning of cartilage were similar to those identified soon after injury and before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the meniscus with ACL injury group underwent ACLR surgery and meniscus suturing; only 3 reported the suture techniques, 34,35,40 2 with inside-out technique, 35,41 and 1 with outside-in technique. 34 Four used semitendinosus and gracilis hamstring tendons for ACLR, 18,28,34,35 2 used bone-patellar tendon-bone, 37,42 and 2 used hamstring for reconstruction. 26,40 There were 4 studies who reported the usage of double bundles in ACLR.…”
Section: Characteristics Of Surgical Techniques In Both Groupsmentioning
confidence: 99%
“…Knowledge of the anterior cruciate ligament (ACL) anatomy is important for understanding its function and the possible pathologies that may involve this structure. ACL injuries can occur simultaneously with damage to the lateral meniscus (LM) and articular cartilage 1 , 2 . Furthermore, in a cohort study of risk factors and predictors of subsequent ACL injury after ACL reconstruction, so-called the MOON study, risk factors for poor outcomes at 10 years after reconstruction included LM procedures and articular cartilage lesions 3 .…”
Section: Introductionmentioning
confidence: 99%